Modelling and calibration of phosphate and glycogen accumulating organism competition for acetate uptake in a sequencing batch reactor - Yagci, N.; Insel, G.; Artan, N.; Orhon, D. (IWA Publishing, 2004)
This paper improves the modeling of enhanced biological phosphate removal, by introducing the mechanistic description of a mixed culture of glycogen and phosphate accumulating organisms competing for acetate, and glycogen metabolism of the latter. A new process stoichiometry is defined for the mixed culture based upon previously developed metabolic concepts and models. The proposed model is tested with and used for the calibration of experimental data generated by a sequencing batch reactor operated with acetate feeding at a P/Ac ratio of 0.05 mgP mg-1COD. The calibration yielded acceptable numerical results for all the model coefficients tested and supported the validity of selected metabolic relationships for process stoichiometry. It also defined conditions that allow the system to sustain glycogen accumulating organisms with significant impact on process behaviour and performance.
Keywords: Time Factors; Acetates; Models, Biological; Waste Disposal, Fluid; Coculture Techniques; Phosphates; Bacteria, Anaerobic; Bioreactors; Calibration; Computer Simulation; Energy Metabolism; Nitrogen Compounds; Glycogen